ANALISA TRANSPOR SEDIMEN DAN PENGARUHNYA TERHADAP PENGERUKAN KOLAM PELABUHAN BATUBARA DI KAWASAN SUKARAJA BANDAR LAMPUNG - Yuda Romdania (UNIVERSITAS LAMPUNG, 2012)
In planning the construction and development of the Port, sedimentation or siltation problemsshould be minimized, especially in swimming harbor to secure and expedite the flow of shipping.Every time the sediment on the seabed will increase, in connection with the, to reduce siltationcaused by sedimentation is by dredging sediment pond Ports. Sediment defined as a collection ofparticle-organic and inorganic particles are irregularly shaped and accumulate extensively incoastal areas. based on Longshore Sediment Transport Table average rate of sediment obtained2176071.364 m3/yr/m. it means, within a period of 1 year, the extent of sediment by 2176071.364m2. And the time when the maximum height allowable sediment was 10.69 years. It means every10.69 years to do the dredging of the sediment on the sea floor, particularly in the harbor pool.